Communicating Environmental Work A case study of challenges related to communicating and integrating Environmental Work in a construction company - Olofsson, Malin; Stenberg, Mikaela (My University, 2018)
The threat about climate changes is one of the most severe environmental issues mankind has ever had to deal with (Naturvårdsverket, 2018) and it affects everything and everyone in one way or another. A big villain is the construction industry, which 2014 stood for 19 % of the total greenhouse gas emissions in Sweden (Lundgren, 2017). However, changes are being done in order to build more environmental friendly and one important part of this change is for construction companies to involve all employees and thereby realize the importance of the human employed by the company as the main resource (Chawla et al., 2018). This thesis aims to investigate how the Environmental Work is communicated and what information is given, within an infrastructure district of a large construction company in Sweden. This in order to help improve the environmental performance by identifying challenges and how these can be overcome in order to obtain the environmental engagement the company is aiming for. It was concluded that more information and knowledge must be mediated in order to increase the consciousness and involvement among the employees. Today there are a rather few communication ways down to the construction sites with a limited amount of information. To increase the knowledge, the investigated district must review how they can communicate the Environmental Work to reach as many as possible and what kind of information being communicated. This thesis highlights an environmental representative and more interactions, possibly made by adapt a sustainable framework where communication and feedback is vital, as important prerequisites and possible solutions for the investigated district.
Keywords: Samhällsbyggnadsteknik; Civil Engineering